Regulation Of The Right Of Restitution For Children As Victims Of Criminal Acts - Andi Dewi Pratiwi; Akhdiari Harpa Dj (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
Victims of criminal acts only get inner satisfaction from the punishment imposed on the perpetrators but do not get anything that has a direct impact on them. The codified concept of Indonesian punishment in the Criminal Code (KUHP) regulates more aspects related to perpetrators of criminal acts and sentencing. Not much regulates the rights of victims of criminal acts. This paradigm shift began to occur after the enactment of Law Number 13 of 2006 concerning the Protection of Witnesses and Victims, where in this Law the rights of Witnesses and Victims began to be considered. Victims are individuals who are harmed materially or immaterially for the occurrence of criminal acts that they receive. In cases of sexual violence against children, it results in losses suffered by child victims in the short and long term which require recovery of the child's condition. Law Number 13 of 2006 juncto Law Number 31 of 2014 concerning Protection of Witnesses and Victims has accommodated restitution.In Law Number 31 of 2014 concerning Protection of Witnesses and Victims, the victims of criminal acts have the right to obtain restitution rights in the form of compensation for loss of property or income, compensation for losses caused by suffering directly related to the crime, and/or reimbursement for medical and/or psychological treatment costs. However, at present the implementation of restitution for victims of crimes against children is considered not optimal, especially regarding the implementation of restitution that can be given to victims.